“The Innovation Imperative”: The Struggle Over Agroecology in the International Food Policy Arena - Anderson, Colin R.; Maughan, Chris (Frontiers in Sustainable Food Systems, 2021)
As the gravity of the global social and ecological crises become more apparent, there is a growing recognition of the need for social transformation. In this article, we use a combination of narrative case study and discourse analysis to better understand how transformative concepts, such as agroecology, are shaped as they as they enter mainstream discursive arenas. We probe the different characteristics of the “innovation frame” and how they qualify and give meaning to agroecology. Our case study narrates the recent emergence of agroecology in the UN space and its relationship to the discursive frame of innovation. We then undertake a systematic discourse analysis of comments provided in an online consultation process on the “Agroecology and Other Innovations” report by the 2019 High-Level Panel of Experts (HLPE) in the World Committee on Food Security. We examine how different actors positioned themselves vis-a-vis the innovation frame and we analyse the discursive strategies used to advance particular political agendas. Our analysis reveals three primary sub-frames within the innovation frame (Evidence; Technology; Rights) which were deployed by both proponents and detractors of agroecology. We focus on the notion of social agency, and its different presentations, within the three sub-frames which raises a number of problematics of the innovation frame, not only for agroecology, but for sustainability transformations more widely.